Marine sources as an unexplored bone tissue reconstruction material -A review. Issue 1 (31st December 2022) - Nayak, Gayatree; Bhuyan, Sanat Kumar; Bhuyan, Ruchi; Sahu, Akankshya; Kar, Dattatreya; Kuanar, Ananya
ABSTRACT: Hard tissue reconstruction of bone has attracted the interest of clinical researchers to overcome the anomalous effect on general well-being. Bone is a supporting skeleton structure that also plays a pivotal role in the normal physiological functioning body. The introduction of bone tissue engineering has been instrumental in overcoming fragmental defined bone to diseases, accidents, or debilitating conditions. For this, various bone grafting materials are used to restore the patency. These various bone grafting options have shown promising results. But the search for ideal grating material continues. However, the available grafting resources may not ensure regeneration. And the grafts like autogenous grafts that provide the capacity, are often, acquired in limited quantity. Its incapacity to fill the defect has led to the requirement of alternative material. Marine sources have shown acceptable clinical outcomes and are rendered safe for use also have a rich calcium phosphate-containing scaffold, over which the new cells are formed owing to its porous and 3D grains. The wide range of available marine sources has been put into clinical trials. The collagen found in the Marine sources has shown comparatively better results than that of the available synthetic alternatives. Graphical abstract: uf0001